THE INFLUENCE OF LEADERSHIP AND WORK ABILITY ON WORK MOTIVATION, AND THEIR IMPLICATIONS ON THE PERFORMANCE OF EDUCATION DEPARTMENT EMPLOYEES IN SOUTH SUMATRA PROVINCE - Dewi Suma; Budi Alamsyah Siregar (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this study was to determine the effect of leadership, work ability, partially or simultaneously on work motivation and to determine the effect of leadership, work ability and work motivation partially or simultaneously on the performance of employees of the South Sumatra Province Education Office. Research method Sampling using proportional sampling technique. The method of data analysis is descriptive analysis and verification with a sample size of 255 respondents, taken from a population of 702. The data analysis method used in this research is Structural Equation Modeling (SEM) with the Analysis of Moment Structure (AMOS) program. Based on the research results, the following findings were obtained; (1) There is a positive and significant influence of leadership on the work motivation of employees in the South Sumatra Province Education Office. (2) There is a positive and significant effect of work ability on the work motivation of employees in the South Sumatra Province Education Office. (3) There is no influence of leadership on the performance of employees in the South Sumatra Provincial Education Office. (4) There is a positive and significant effect of work ability on the performance of employees in the South Sumatra Province Education Office. (5) There is a positive and significant influence of work motivation on the performance of employees in the South Sumatra Province Education Office. The conclusion of the research is to increase work motivation, the variable that must be improved is the work ability of the employees of the South Sumatra Province Education Office. Meanwhile, to improve the performance of employees at the South Sumatra Provincial Education Office, what must be improved first is the work ability of the employees of the South Sumatra Provincial Education Office.